From Pesantren to Nation: KH. Ghalib’s Contribution to Islamic Education in Pringsewu - Wahyu Agil Permana (UIN Imam Bonjol Padang, 2024)
Islamic boarding school (pesantren) is one of the oldest educational institutions in Indonesia plays a centralized role in cultivating scientific tradition as well as building characterization of the nation. On its development, pesantren goes beyond merely religious education. Pesantren also makes contribution in social cultural to the society. One of the most important figure in Islamic education in Pringsewu, Lampung is KH. Ghalib. KH. Ghalib is an Islamic scholar that was born in Mojosantren, Krian, East Java. His presence in Pringsewu acted as a beacon in the darkness at the time. K.H. Ghalib left a mark on history, especially to Islamic education in Pringsewu, where its contribution is still widely felt. This research aims to study the role of KH. Ghalib in creating and developing pesantren in Pringsewu along with its impact toward the life of the society. The methodology used in this research is historical method which consists of four steps; heuristic, criticism, interpretation and histiography. The result of this research shows that KH. Ghalib plays a significant role in the development of Islamic education in Pringsewu. It can be concluded that KH. Ghalib provides a significant contribution to the development of Islamic education in Pringsewu also strengthens the role of pesantren as an educational institution that contributes to build the nation’s character.